2021
DOI: 10.1186/s13045-021-01089-z
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative circulating tumor DNA as markers of recurrence risk in stages II to III colorectal cancer

Abstract: Background Precise methods for postoperative risk stratification to guide the administration of adjuvant chemotherapy (ACT) in localized colorectal cancer (CRC) are still lacking. Here, we conducted a prospective, observational, and multicenter study to investigate the utility of circulating tumor DNA (ctDNA) in predicting the recurrence risk. Methods From September 2017 to March 2020, 276 patients with stage II/III CRC were prospectively recruited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
119
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 112 publications
(132 citation statements)
references
References 27 publications
13
119
0
Order By: Relevance
“…Other groups have similarly corroborated a low recurrence risk in ctDNA-negative patients for resected stage II–III CRC (2-year RFS rate of 89.4%) based on blood draws as early as 3–7 days postoperatively [ 26 ], whereas postoperative ctDNA-positivity has been associated with increased recurrence risk using tumor-informed assays in localized, resected CRC [ 23 , 34 , 35 , 36 , 37 , 38 , 39 ].…”
Section: Detection Of Minimal Residual Disease and Recurrences In Resected Stage I–iii Colorectal Cancermentioning
confidence: 92%
See 1 more Smart Citation
“…Other groups have similarly corroborated a low recurrence risk in ctDNA-negative patients for resected stage II–III CRC (2-year RFS rate of 89.4%) based on blood draws as early as 3–7 days postoperatively [ 26 ], whereas postoperative ctDNA-positivity has been associated with increased recurrence risk using tumor-informed assays in localized, resected CRC [ 23 , 34 , 35 , 36 , 37 , 38 , 39 ].…”
Section: Detection Of Minimal Residual Disease and Recurrences In Resected Stage I–iii Colorectal Cancermentioning
confidence: 92%
“…Although it has been well described that ctDNA analysis in plasma samples minimizes the dilution of tumor-derived DNA and optimizes the sensitivity of ctDNA analysis over serum, a question remains as to the optimal timing of the blood collection for ctDNA assessment [ 152 , 153 ]. It has been shown that preoperative ctDNA positivity is predictive of recurrence risk compared to preoperative ctDNA negativity in CRC patients with both localized and metastatic disease [ 26 , 154 , 155 ]. However, most localized CRC cases are preoperative ctDNA positive (up to 90%) [ 27 ], and the constellation of evidence supports that postoperative ctDNA in resected, stage I–III CRC is most predictive of RFS ( Table 1 ).…”
Section: Future Considerationsmentioning
confidence: 99%
“…18 Several groups have also provided evidence supporting that ctDNA could reflect the existence of minimal residual disease postoperatively. [19][20][21] Moreover, the serial ctDNA testing may help monitor treatment efficacy, with the early change in ctDNA serving as a marker of clinical response. 22 23 And ctDNA could track RAS clones to monitor drug resistance or the potential to receive anti-EGFR rechallenge.…”
Section: Gi Cancermentioning
confidence: 99%
“…ctDNA is tumor-released single- or double-stranded DNA that enters the bloodstream and can be detected for diagnosis, guidance of treatment, and monitoring of disease progression. Recently, ctDNA has been used to guide clinical decision-making in several tumor types including CRC ( Chen et al, 2021 ), NSCLC ( Song et al, 2020 ), and metastatic breast cancer (MBC) ( Darrigues et al, 2021 ). In CRC, postoperative serial ctDNA detection identified recurrence before radiological imaging and was predictive of high relapse risk ( Chen et al, 2021 ).…”
Section: Liquid Biopsymentioning
confidence: 99%
“…Recently, ctDNA has been used to guide clinical decision-making in several tumor types including CRC ( Chen et al, 2021 ), NSCLC ( Song et al, 2020 ), and metastatic breast cancer (MBC) ( Darrigues et al, 2021 ). In CRC, postoperative serial ctDNA detection identified recurrence before radiological imaging and was predictive of high relapse risk ( Chen et al, 2021 ). ctDNA has suggested a novel therapeutic rechallenge strategy for CRC based on evidence that resistance mechanisms to anti-EGFR therapy extinguish over time off of that therapy ( Misale et al, 2014 ; Parseghian et al, 2019 ; Sartore-Bianchi et al, 2021 ).…”
Section: Liquid Biopsymentioning
confidence: 99%